PTH-007 Endoscopic removal of adenomas involving appendix base is technically feasible using full thickness resection device. (June 2019) - Boger, Phil; Rahman, Imdadur; Chedgy, Fergus; Green, Susi; Phull, Perminder; Thomas-Gibson, Siwan; Patel, Praful
Abstract : Introduction: Endoscopic resection of adenomas involving the appendiceal base is challenging and often technically impossible with resultant necessity for surgery. Endoscopic full thickness resection (eFTR) using the full thickness resection device (FTRD) is a novel technique for removing lesions in the colo-rectum unresectable by conventional methods. We report use of this technique and outcomes for adenomas involving the appendiceal base. Methods: Data was collected and analysed on patients who underwent eFTR of adenomas involving the appendix base in the UK from April 2015 – January 2019. Main outcome measures were technical success, procedural time, specimen size, R0 resection, endoscopic clearance, and adverse events including appendicitis, and need for surgery. Results: 10 cases were identified across 4 sites where eFTR was attempted for adenoma at the appendix base. Mean patient age was 68 years (range 57–78). 3/10 had previous attempts at EMR and 2/10 had prior appendicectomy. In 9/10 patients the lesion was reached with the FTRD, with failure of insertion in 1/10 due to sigmoid diverticulosis. The procedure was technically successful in 9/9 patients. Median procedure time was 72 minutes (50–97) and median resection time 6 minutes (4–17). Antibiotics were given in all cases. Median hospital stay was 1 day (1–3). Median specimen size was 26 mm (15–35), and full thickness resection was achieved in 7/9 and R0 resection in 6/9. In those where R0 resection was not achieved, 2/3 had residual lesion at follow up; one residual lesion removed by snare, one had clip still in situ and awaiting use of clip cutter to facilitate residual polyp removal. Overall endoscopic clearance rate to date is 89% (8/9). One patient developed appendicitis at day 6 which required surgery to remove a gangrenous appendix. The patient made an uneventful recovery. Appendicitis rates for this cohort was therefore 14.2% (1/7) when those with prior appendicectomy were excluded. No other complications occurred. Conclusions: Removal of adenomas at the appendix base by eFTR is technically feasible and can avoid the need for surgery. Rates of appendicitis in our cohort are significant and similar to published data 1, suggesting the need for careful consent and close observation post procedure. Reference: Schmidt A, et al. Gut 2018; 67: 1280–1289.